THE EFFECT OF CHEST PHYSIOTHERAPY ON THE EFFECTIVENESS OF THE AIRWAY AMONG PNEUMONIA PATIENTS AT THE CHILDREN'S ROOM OF BANGIL REGIONAL GENERAL HOSPITAL - Erik Kusuma; Ayu Dewi Nastiti; R.A. Helda Puspitasari (UNEJ e-Proceeding, 2022)
Pneumonia is inflammation of the lungs that results in increased production of secretions. If it is not balanced with the individual's ability to excrete secretions, it will interfere with the effectiveness of the airway. This study aim to determine the effect of chest physiotherapy on the effectiveness of the airway in children with pneumonia. A quasi-experimental design was adopted for the study. Purposive sampling technique was adopted to select 18 samples for the study, 9 samples each for the experimental (chest physiotherapy) and control (SOP) groups. The effects were assessed using airway effectiveness observation sheet. The data obtained were analyzed by means of a dependent and independent T-test.The study showed that there were a significant in the mean of airway effectiveness score before and after the procedure in both groups (p 0.007 <0.05). However, in experimental group the decrease of airway effectiveness scores were more significant. The results of the independent T-test obtained p 0.04 (<0.05) so that it was concluded that there was an effect of chest physiotherapy on the effectiveness of the airway in children with pneumonia in the Children's Room at Bangil Hospital. Chest physiotherapy, which combines postural drainage, vibration and percussion techniques, is useful for treating airway clearance disorders in children who have not been able to cough effectively. In practice, chest physiotherapy can be combined with other technique according to the Standard Operating Procedure (SOP) applied by the hospital.Keywords: Chest Physiotherapy, Effectiveness of the Airway, Pneumonia